Kölner Kunst Markt KKM '71. - Brusberg, Dieter; Art Cologne, Köln; Kunsthalle Köln, Köln (Köln : Kunstmarkt Köln, 1971)
Abrahams, Ivor ; Accardi, Carla ; Adami, Valerio ; Adzak, Roy ; Aeppli, Eva ; Akrithakis, Alexis ; Alechinsky, Pierre ; Alexander, Peter ; Allen, Bill ; Alt, Otmar ; Altenbourg, Gerhard ; Andre, Carl ; de Andrea, John ; Anselmo, Giovanni ; Antes, Horst ; Arakawa, Shusaku ; Arman ; Armitage, Kenneth ; Artschwager, Richard ; Atkinson, Terry ; Attersee, Christian Ludwig ; Aubertin, Bernard ; Avramidis, Joannis ; Baehr, Ulrich ; Baer, Jo ; Baldessari, John ; Baldwin, Michael ; Bannard, Walter Darby ; Barni, Roberto ; Barry, Robert ; Baruchello, Gianfranco ; Baschang, Hans ; Baschlakow, Alexej Iljitsch ; Baselitz, Georg ; Baumeister, Willi ; Beasley, Bruce ; Becher, Bernd & Hilla ; Beckmann, Max ; Bell, Larry ; Bellmer, Hans ; Bengston, Billy Al ; Berges, Werner ; Berkovitz, Martin ; Bernhard, Franz ; Berrocal, Miguel ; Beuys, Joseph ; Bill, Max ; Birgfeld, Detlef ; Bochner, Mel ; De Boer, Saskia ; Boetti, Alighiero ; Bohrmann, Karl ; Bollinger, Bill ; Boltanski, Christian ; Bonalumi, Agostino ; Bonato, Victor ; Bontecou, Lee ; Botero, Fernando ; Brecht, George ; Breder, Hans ; Broodthaers, Marcel ; Brouwn, Stanley ; Brüning, Peter ; Buchholz, Erich ; Buckley, Steven ; Buren, Daniel ; Bury, Pol ; Buscioni, Umberto ; Bush, Jack ; Buthe, Michael ; Byars, James Lee ; Calderara, Antonio ; Calzolari, Pierpaolo ; Camesi, Gianfredo ; Canogar, Rafael ; Carder, Malcolm ; Caro, Anthony ; Castro, Lourdes ; Castro-Cid, Enrique ; Cavaliere, Alik ; Ceroli, Mario ; César ; Chaissac, Gaston ; Chamberlain, John ; Chillida, Eduardo ; Christensen, Dan ; Christo ; Clarke, John Clem ; Colombo, Gianni ; Colverson, Ian ; Conlon, Bill ; Copley, William ; Cote, Alan ; Cruz-Diez, Carlos ; D'Arcangelo, Allan ; Dahmen, Karl Fred ; Danby, Ken ; Daphnis, Nassos ; Darboven, Hanne ; Davis, Ron ; etc.
Kölner Kunstmarkt KKM '71, Kunsthalle Köln, 5. bis 10. Oktober 1971
Duits
kunstcatalogus